Two in One: Light as a Tool for 3D Printing and Erasing at the Microscale. Issue 40 (16th August 2019) - Batchelor, Rhiannon; Messer, Tobias; Hippler, Marc; Wegener, Martin; Barner‐Kowollik, Christopher; Blasco, Eva
Abstract: The ability to selectively remove sections from 3D‐printed structures with high resolution remains a current challenge in 3D laser lithography. A novel photoresist is introduced to enable the additive fabrication of 3D microstructures at one wavelength and subsequent spatially controlled cleavage of the printed resist at another wavelength. The photoresist is composed of a difunctional acrylate cross‐linker containing a photolabile o ‐nitrobenzyl ether moiety. 3D microstructures are written by photoinduced radical polymerization of acrylates using Ivocerin as photoinitiator upon exposure to 900 nm laser light. Subsequent scanning using a laser at 700 nm wavelength allows for the selective removal of the resist by photocleaving the o ‐nitrobenzyl group. Both steps rely on two‐photon absorption. The fabricated and erased features are imaged using scanning electron microscopy (SEM) and laser scanning microscopy (LSM). In addition, a single wire bond is successfully eliminated from an array, proving the possibility of complete or partial removal of structures on demand. Abstract : A novel photoresist enabling the additive fabrication of 3D microstructures using one wavelength and subsequent spatially controlled cleavage of the printed resist using another wavelength is introduced. Microstructures are written upon exposure to 900 nm laser light and subsequent scanning using a laser at 700 nm wavelength allows for the selective removal of the written resist via a photocleavage reaction.